IMPLEMENTASI KEPUTUSAN DIRJEN BIMAS KATOLIK KEMENTERIAN AGAMA RI NOMOR 6B TAHUN 2019 TENTANG REKRUTMEN DAN PEMBAYARAN HONORARIUM PENYULUH AGAMA KATOLIK NON PEGAWAI NEGERI SIPIL DI KABUPATEN KARANGANYAR - Agustinus Triwiyarso (Master of Public Administration, Universitas Slamet Riyadi, 2020)
Honorarium Payment Policy for Non-PNS Catholic Religious Instructor refers tothe Decree of the Director General of Catholic Community Guidance of theMinistry of Religion of the Republic of Indonesia Number 6B 2019.This research used a qualitative method through descriptive analysis with a casestudy model.The focus of this research is to analyze the implementation of thepolicy of giving honorariums for non-civil servant Catholic religious counselorsin Karanganyar Regency by using factors initiated by George C. Edward III,namely communication, resources, disposition and bureaucratic structure thatplay a role in policy implementation. The four factors Edward III's ideas are verymeaningful for policy implementation.The results of this study indicate that the implementation of the policy of payinghonorariums for non-civil servant Catholic religious extension officers inKaranganyar Regency has fulfilled the four elements of public policyimplementation in the Edward III theory, although it is not yet perfect.Communication in this case consistency is the weakest element in implementingthe policy of granting Honorarium for Non-PNS Catholic Religious Instructor.